Dermoscopic features in different types of lichen planus: a case series - Singh, Sudhir Kumar; Kharabanda, Akshara; Kundalia, Anchal (International Journal of Research in Dermatology, 2025)
Lichen planus is a chronic inflammatory skin disorder that affects the skin, scalp, nails, and mucous membranes. It is characterized by distinctive purplish, flat-topped papules, often accompanied by intense pruritus. The etiology of LP remains largely idiopathic, although immune-mediated mechanisms, including T-cell mediated responses, are thought to play a significant role in its pathogenesis. Its prevalence is estimated at 0.22% to 1% of the adult population, with oral lichen planus occurring in 1-4% of individuals. Dermoscopy is a useful non-invasive tool for evaluating lichen planus, allowing detailed visualization of skin lesions and aiding in diagnosis. This technique is particularly beneficial in cases where clinical evaluation alone might be insufficient. Dermoscopy not only supports the diagnosis but also provides insights into disease activity and progression, and identifying complications such as scarring or malignant transformation in rare cases. making it an essential tool for dermatologists in managing lichen planus. This paper explores various dermoscopic findings associated with different variants of lichen planus, including classical, actinic, planopilaris, pigmentosus and hypertrophic lichen planus (HLP).